Examining the perception of Islamic banks customers in Kedah state on the Mudarabah contract and its application by Islamic banks - Gaani, Ismail Ahmed Ali (2015)
It is undeniable that the impressive growth and development of Islamic financial institutions in Malaysia is due to the fact that Malaysian government put in place an effective and comprehensive legal framework. 2013, was a landmark in Malaysia Islamic financial service industry, where Malaysia parliament enacted Islamic Financial Service Act (IFSA) that ensures shariah compliant, financial stability and protect the rights and interest of financial consumers. Under IFSA, Islamic banks should use only mudarabah in their investment accounts. Therefore, the overall aim of this study is to examine the perceptions of Islamic banks customers on the concept, applications and implications of mudarabah (profit sharing) contract. The study has used a survey, where questionnaires were distributed to 200 respondents. Descriptive statistics, factor analysis, independent t-test and ANOVA were used in data analysis. The results of factor analysis reveal that highly level of awareness among customers on the concept of mudarabah, its applications in Islamic banking products and services; and its implications to customers, for e.g. in the form of offering high returns positively influence customers perception towards mudarabah related products and services. In other words, the more the customers are informed about the concept of mudarabah, its application in banking products and its implication to them, the more positive perception they have towards mudarabah related products and services. In addition, the independent t-test and ANOVA results reveal that there are no significant difference between gender, race, marital status, and job sectors in relation to the level of their awareness towards mudarabah contract. However there are significant different between customer‟s level of education and level of income and customer‟s perception towards mudarabah related products. Meaning the highly educated and highincome respondents are more aware about the concept of mudarabah, its applications and implications. These in turns positively influence their perception towards mudarabah related products and services. Therefore, policy makers and financial institutions should find ways to increase on the level of awareness of customers on the concept of mudarabah, its applications and implications. BNM should issue effective guidelines for Islamic banks to explain to customers the concept, applications and implications of any contract before offering the products to the customers. Bankers should educate their customers on various Islamic contracts they used so that the customers become fully aware on their concept, applications and implications before subscribing to any Islamic banking products and services